EFEITO DA APLICAÇÃO DE INOCULANTES SOBRE O PERFILHAMENTO DO CAPIM-MARANDU. - MACHADO, Dayane Camargo; TENÓRIO, Kamila de Paula; RODRIGUES Nicolly Queiroz; OLIVEIRA, Thayná Fernanda Silva; ROCHETTI, Ana Carolina Alves (ANAIS DO ENIC, 2023)
-